2010
DOI: 10.1073/pnas.0910421107
|View full text |Cite
|
Sign up to set email alerts
|

Picomole-scale characterization of protein stability and function by quantitative cysteine reactivity

Abstract: The Gibbs free energy difference between native and unfolded states ("stability") is one of the fundamental characteristics of a protein. By exploiting the thermodynamic linkage between ligand binding and stability, interactions of a protein with small molecules, nucleic acids, or other proteins can be detected and quantified. Determination of protein stability can therefore provide a universal monitor of biochemical function. Yet, the use of stability measurements as a functional probe is underutilized, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
3
28
0
1
Order By: Relevance
“…The measurement of protein stability typically also has required relatively large amounts of protein and low-throughput instrumentation and, consequently, has not been widely used as a tool to assess function. However, recently a number of techniques that allow protein stabilities to be determined with small amounts of material in a high-throughput manner have been developed (8)(9)(10)(11)(12). One such method is based on extrinsic fluorescent dyes that monitor protein (un)folding (2,3,13).…”
mentioning
confidence: 99%
“…The measurement of protein stability typically also has required relatively large amounts of protein and low-throughput instrumentation and, consequently, has not been widely used as a tool to assess function. However, recently a number of techniques that allow protein stabilities to be determined with small amounts of material in a high-throughput manner have been developed (8)(9)(10)(11)(12). One such method is based on extrinsic fluorescent dyes that monitor protein (un)folding (2,3,13).…”
mentioning
confidence: 99%
“…10,16,17 Both approaches are high-throughput and require less material than conventional methods. However, the labeling mechanism of each assay differs.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we measured the thermal stability of GPA1-GDP and GPA1-GTP␥S. For this experiment, GPA1 was incubated at a range of temperatures with a fluorescent label that modifies cysteine residues that are exposed to the solvent either by surface location or by protein unfolding (15,27). We found that the unactivated form of GPA1 is less stable than the activated form of GPA1, with the median melting temperature increasing from 46°C with GDP to 53°C with GTP␥S (Fig.…”
Section: Resultsmentioning
confidence: 99%